Fast, Sensitive, and Inexpensive Alternative to Analytical Pigment HPLC:Quantification of Chlorophylls and Carotenoids in Crude Extracts by Fitting with Gauss Peak Spectra - Küpper, Hendrik; Seibert, Sven; Parameswaran, Aravind (My University, 2007)
Quantification of pigments in complex mixtures is an important task in the physiology of photosynthetic organisms, because pigment composition differs depending on the species, tissue, and physiological state. Currently available methods, however, are either limited to very few pigments (classical UV/vis spectroscopic methods), or they are time-consuming, labor intensive, or costly (e.g., HPLC). Here we describe a UV/vis spectrophotometric method that is capable of a rapid (1 min/sample) and inexpensive (
Keywords: 570